Möjligheter att förändra/s: En berättelse om rörelser, rum och upplevelser av kön - Lundgren, Anna Sofia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2002)
There has been a certain debate in swedish media concerning the harsh climate among young people of today. One of the proofs of this being so has often enough been examples where young women tell about the increase of fights between girls taking place in public. For the sake of presenting a fuller description of an event with some importance for how to think about body scripts, the public, and gender, this article tries to bring together views and opinions collected from several informants but reorganised in a literary style. The aim is to describe one specific situation that ended in a fight between two teenage girls, and to ask questions about what this experience might mean in terms of experienced gender belongings and possibilities.